A monolithic K-band phase-locked loop for microwave radar application *Project supported by the National High-Tech Research and Development Program of China (No. 2013AA014101). (February 2017) - Zhou, Guangyao; Ma, Shunli; Li, Ning; Ye, Fan; Ren, Junyan
Abstract: A monolithic K-band phase-locked loop (PLL) for microwave radar application is proposed and implemented in this paper. By eliminating the tail transistor and using optimized high- Q LC -tank, the proposed voltage-controlled oscillator (VCO) achieves a tuning range of 18.4 to 23.3 GHz and reduced phase noise. Two cascaded current-mode logic (CML) divide-by-two frequency prescalers are implemented to bridge the frequency gap, in which inductor peaking technique is used in the first stage to further boost allowable input frequency. Six-stage TSPC divider chain is used to provide programmable division ratio from 64 to 127, and a second-order passive loop filter with 825 kHz bandwidth is also integrated on-chip to minimize required external components. The proposed PLL needs only approximately 18.2 μ s settling time, and achieves a wide tuning range from 18.4 to 23.3 GHz, with a typical output power of −0.84 dBm and phase noise of −91.92 dBc/Hz @ 1 MHz. The chip is implemented in TSMC 65 nm CMOS process, and occupies an area of 0.56 mm 2 without pads under a 1.2 V single voltage supply.